PENGARUH KEPEMIMPINAN TERHADAP KEDISIPLINAN PEGAWAI DI DINAS ADMINISTRASI KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TAKALAR - Ekayanti, Reski; Malik, Ihyani; P, Hafiz Elfiansya (Universitas Muhammadiyah Makassar, 2022)
The objective of this research is to find out the influence of Leadership on Employee Dicipline in population and Civil Registration Agency of Takalar Regency. The type of the research is quantitative with the type of survey research and collection techniques using observation, questionnaire and documentation techniques. The informants involved in this research are seventy five people in the population and civil Registration of Takalar Regency. The sample of the research was selected by using saturated sample technique. The results of this research show that the leadership is a responsibility that must be carried out in addition to leadership responsibilities can also be called an activity carried out by the leader by carrying out his leadership duties has a big influence on employee discipline, so the discipline of employees is good enough because the leadership can be said firmly in doing the action. The leadership variables have a positive influence on the Dicipline of Employees of population and civil Registry of Takalar Regency. Keywords: influence, leadership, discipline.